Association between the force-velocity profile and performance variables obtained in jumping and sprinting in elite female soccer players - Marcote-Pequeno, R.; Garcia-Ramos, A.; Cuadrado-Penafiel, V.; González-Hernández, J. M.; Gómez, M. A.; Jiménez-Reyes, P. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To quantify the magnitude of the association between the same variables of the force-velocity (FV) profile and the performance variables (unloaded-squat-jump height and 20-m sprint time) obtained during jumping and sprinting testing and to determine which mechanical capacity (ie, maximum force [F0], maximum velocity [V0], or maximum power [Pmax]) presents the highest association with the performance variables. Methods: The FV profile of 19 elite female soccer players (age 23.4 [3.8] y, height 166.4 [5.6] cm, body mass 59.7 [4.7] kg) was determined during the jumping and sprinting tasks. The F0, V0, FV slope, Pmax, and FV imbalance (difference respect to the optimal FV profile in jumping and the decrease in the ratio of horizontal force production in sprinting) were determined for each task. Results: Very large correlations between both tasks were observed for Pmax (r = .75) and the performance variables (r = -.73), as well as moderate correlations for V0 (r = .49), while the F0 (r = -.14), the FV slope (r = -.09), and the FV imbalance (r = .07) were not significantly correlated between both tasks. The Pmax obtained during each specific task was the mechanical capacity most correlated with its performance variable (r = .84 in jumping and r = .99 in sprinting). Conclusions: The absence of significant correlations between some of the FV relationship parameters suggests that, for an individualized training prescription based on the FV profile, both jumping and sprinting testing procedures should be performed with elite female soccer players.